Embolic strokes of undetermined source: prevalence and patient features in the ESUS Global Registry - Perera, Kanjana; Vermehren, Philipp (International journal of stroke, 2016)
BackgroundRecent evidence supports that most non-lacunar cryptogenic strokes are embolic. Accordingly, these strokes have been designated as embolic strokes of undetermined source (ESUS).AimsWe undertook an international survey to characterize the frequency and clinical features of ESUS patients across global regions.MethodsConsecutive patients hospitalized for ischemic stroke were retrospectively surveyed from 19 stroke research centers in 19 different countries to collect patients meeting criteria for ESUS.ResultsOf 2144 patients with recent ischemic stroke, 351 (16%, 95% CI 15% to 18%) met ESUS criteria, similar across global regions (range 16% to 21%), and an additional 308 (14%) patients had incomplete evaluation required for ESUS diagnosis. The mean age of ESUS patients (62 years; SD?=?15) was significantly lower than the 1793 non-ESUS ischemic stroke patients (68 years, p?≤?0.001). Excluding patients with atrial fibrillation (n?=?590, mean age?=?75 years), the mean age of the remaining 1203 non-ESUS ischemic stroke patients was 64 years (p?=?0.02 vs. ESUS patients). Among ESUS patients, hypertension, diabetes, and prior stroke were present in 64%, 25%, and 17%, respectively. Median NIHSS score was 4 (interquartile range 2?8). At discharge, 90% of ESUS patients received antiplatelet therapy and 7% received anticoagulation.ConclusionsThis cross-sectional global sample of patients with recent ischemic stroke shows that one-sixth met criteria for ESUS, with additional ESUS patients likely among those with incomplete diagnostic investigation. ESUS patients were relatively young with mild strokes. Antiplatelet therapy was the standard antithrombotic therapy for secondary stroke prevention in all global regions.